The requirements of the international standards on traceability of measurement results at OJSC «BSW – Management Company of Holding «BMC» - E. V. Borisenko; I. V. Buyanova (Литьë и металлургия, 2019)
A serious barrier to the sale of products on the market is the trust in organizations that perform measurements during product testing, as well as calibration (verification) of the used measuring instruments. Confidence and recognition of measurement results at the international level is ensured through an accreditation mechanism. To ensure effective functioning at the international level, accreditation organizations enter into a multilateral agreement that provides for the use of common standards in the conduct of accreditation. One of the important requirements of these standards is the implementation and demonstration of metrological traceability, which is a tool for ensuring the uniformity of measurements.